2003
DOI: 10.1038/sj.tpj.6500208
|View full text |Cite
|
Sign up to set email alerts
|

The human dopamine D4 receptor repeat sequences modulate expression

Abstract: Genetic studies have implicated a polymorphic repeat sequence in exon 3 of the human dopamine D4 receptor in various behavioral and psychiatric disorders. Functionally various repeat variants are nearly identical, but whether these have different effects on gene expression has not been studied. To study the role of the repeat sequences on expression independently from its structural and functional effects at the protein level, we introduced these sequences immediately upstream of the promoter and in the 3 0 un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
150
0
4

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 202 publications
(160 citation statements)
references
References 32 publications
6
150
0
4
Order By: Relevance
“…To date no major functional consequences have been associated with the repeat sequence, although small effects on signaling efficacy and translation have been reported by us (23,38). Here we show relatively robust differences in the ability of the three major variants to be up-regulated through the pharmacological chaperone effect.…”
Section: Fig 5 Ligand-mediated Up-regulation/rescue Of Drd4 (A-d) Amentioning
confidence: 46%
See 1 more Smart Citation
“…To date no major functional consequences have been associated with the repeat sequence, although small effects on signaling efficacy and translation have been reported by us (23,38). Here we show relatively robust differences in the ability of the three major variants to be up-regulated through the pharmacological chaperone effect.…”
Section: Fig 5 Ligand-mediated Up-regulation/rescue Of Drd4 (A-d) Amentioning
confidence: 46%
“…Because the baseline levels of expression for the three variants are similar the latter seems more plausible. However, it should also be considered that baseline expression levels are the product of control at various levels, including transcription and translation that may differ between receptor variants (38). Whether the differences between receptor variants revealed by the pharmacological chaperone effect relate to the observed genetic associations of this receptor to attention deficit hyperactivity disorder and behavioral traits like novelty seeking/exploratory behavior remains to be elucidated.…”
Section: Fig 5 Ligand-mediated Up-regulation/rescue Of Drd4 (A-d) Amentioning
confidence: 99%
“…[110][111][112][113] One avenue of future research would be to examine all three loci in a single haplotype for their joint effect on expression. It would be of considerable value to know whether these various polymorphisms additively contribute to expression or is one locus a major determinant in regulating protein receptor levels?…”
Section: Drd4 Haplotypesmentioning
confidence: 99%
“…DRD4 exon III repeat region has functional consequences Studies of G protein coupling, 110 cyclic AMP synthesis, 111 in vitro expression 112 and chaperone-induced folding 113 provide increasingly solid evidence that the shorter exon III repeats code for a more efficient gene at the level both of transcription, translation and second messenger generation compared to the D4.7 repeat.…”
mentioning
confidence: 99%
“…The dopamine receptor D4 gene (DRD4) has a VNTR polymorphism in the third exon, which is part of the third intracellular loop of the receptor, and may therefore have functional relevance [Asghari et al, 1995;Schoots and Van Tol, 2003]. Recent meta-analyses confirmed that the 7-repeat allele increased the risk of developing ADHD 1.4-2.0 times [Faraone et al, 2001;Maher et al, 2002].…”
Section: Introductionmentioning
confidence: 99%